The Role of Intellectual Capital and Economic Performance in Developing Villages through Utilization of Village Funds - Diatmika, I Putu Gede (Jati: Jurnal Akuntansi Terapan Indonesia, 2023)
This study examines intellectual capital, village economic performance, community engagement, and government involvement in village development utilising village finances in Buleleng Regency. The quantitative research method used in this study is descriptive. This study analyses quantitative data using SEM. The outer and inner models comprise partial least squares structural equation modelling (PLS-SEM). The study found that technology, particularly the internet, improves government operations by improving monitoring and evaluating regulatory actions. Media information can streamline market procedures and enable seamless modifications. The economic performance of a village can contribute to its overall growth through important measures. These indicators include rural economic empowerment, community development institutions, and village administration intellectual capital. Technology can improve and streamline village officials' duties in Buleleng Regency. The SILAKUDES Application manages village district services comprehensively. This app aims to help village administrators manage cash and meet community needs faster. This includes simplifying micro and small business permit applications.